2008
DOI: 10.1016/j.pain.2007.05.023
|View full text |Cite
|
Sign up to set email alerts
|

IL-1ra alleviates inflammatory hyperalgesia through preventing phosphorylation of NMDA receptor NR-1 subunit in rats

Abstract: Although it has been shown that pro-inflammatory cytokines such as interleukin-1beta (IL-1beta) facilitate perception of noxious inputs at the spinal level, the mechanisms have not been understood. This study determined the cell type that produces IL-1beta, the co-localization of IL-1 receptor type I (IL-1RI) and Fos and NR1 in the spinal cord, and the effects of IL-1 receptor antagonist (IL-1ra) on NR1 phosphorylation and hyperalgesia in a rat model of inflammatory pain. Phosphorylation of NR1, an essential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 33 publications
9
158
0
Order By: Relevance
“…Surprisingly, only a handful of studies directly address the impacts created by these cytokines on spinal glutamatergic synaptic activities. In a rat model of inflammatory pain induced by injecting complete Freund's adjuvant, IL-1␤ produced by activated astrocytes increased phosphorylation of NMDA receptors in the spinal dorsal horn (62). In another model of inflammatory pain induced by carrageenan, it was demonstrated that elevated levels of TNF␣ in the spinal dorsal horn increase AMPA receptor activities by enhancing trafficking of AMPA receptors from the cytosol to the membrane (63).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, only a handful of studies directly address the impacts created by these cytokines on spinal glutamatergic synaptic activities. In a rat model of inflammatory pain induced by injecting complete Freund's adjuvant, IL-1␤ produced by activated astrocytes increased phosphorylation of NMDA receptors in the spinal dorsal horn (62). In another model of inflammatory pain induced by carrageenan, it was demonstrated that elevated levels of TNF␣ in the spinal dorsal horn increase AMPA receptor activities by enhancing trafficking of AMPA receptors from the cytosol to the membrane (63).…”
Section: Discussionmentioning
confidence: 99%
“…This process is because of most of the inflammatory mediators released by reactive microglia interacting with membrane receptors of nociceptive second-order projection neurons in the dorsal horn of the spinal cord, causing hyperexcitability and sensitization among them. [47][48][49][50] It is important to mention that traumatic spinal cord injury also induces spinal microglial cell reactivation, which leads to an increase of inflammatory mediators and hyperexcitability in spinal nociceptive projection neurons. 18 After microglial cell reactivation is produced by an injury in the nociceptive somatosensory system, a long-standing reactivation of spinal astrocytes occurs (4150 days post-injury), inducing hypertrophy within (increase in vimentin and GFAP glial fibrillary acidic cytoskeleton proteins) and a release of inflammatory mediators that contribute to hyperexcitability and sensitization of nociceptive neurons in the dorsal horn of the spinal cord.…”
Section: Molecular Neuroplasticity Of Ascending Pain Pathway In Injurmentioning
confidence: 99%
“…18 After microglial cell reactivation is produced by an injury in the nociceptive somatosensory system, a long-standing reactivation of spinal astrocytes occurs (4150 days post-injury), inducing hypertrophy within (increase in vimentin and GFAP glial fibrillary acidic cytoskeleton proteins) and a release of inflammatory mediators that contribute to hyperexcitability and sensitization of nociceptive neurons in the dorsal horn of the spinal cord. [47][48][49][50][51] On the other hand, neuropathic pain is also promoted by spinal cord injury. It is well known that spinal cord injury causes the astrocyte and microglial cell reactivation and the generation and release of several soluble factors such as cytokines (IL1, IL6 and TNF-alpha), chemokines (CCL2) and prostaglandins (PGE2) that interact with nociceptive projection neurons and afferent primary nerve fibers at the dorsal horn of spinal cord segments located rostral and caudal to the lesion site, causing hyperexcitability of these nociceptive neurons and pain neurotransmission in the dorsal horn.…”
Section: Molecular Neuroplasticity Of Ascending Pain Pathway In Injurmentioning
confidence: 99%
“…These cells produces a number of algesic substances such as the proinflammatory cytokines interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and IL-6 to promote spinal transmission and processing of noxious signals [1,2]. It is reported that IL-1β is up-regulated in spinal astrocytes to increase NMDA NR1 phosphorylation, an essential subunit of the N-methyl Daspartate receptor (NMDAR), which in turn promote pain in an inflammatory pain rat model [3][4][5][6] . IL-17A, recently found in astrocytes of patients with multiple sclerosis [7], increase in concentration in the spinal cord of rats with nerve injury [8].…”
Section: Introductionmentioning
confidence: 99%